ADMINISTRATION INVENTORY SYSTEM DRUGS ON CHEMICAL PHARMACIES FARMA (PERSERO) - Fajar Nugroho; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2002)
In today's era of globalization of the world to simplify and speed up a job that can produce accurate information is required. Indispensable role in solving computer-related work with a variety of data storage and updating of existing data. Apotek Kimia Farma (Persero) Tbk No. 47 is a company engaged in the sale, compounding, and processing of drugs and health equipment. The company is developing in line with the increasing demand from consumers, clinics, hospitals and physicians have subscribed. Pharmacy is also a certain place, where do the work of pharmacy and distribution of pharmaceutical supplies to the public. Our society is a decade ahead in dealing with health conditions are still expected to focus efforts on prevention rather than treatment. For that Kimia Farma Apotek (Persero) Tbk No. 47 tried to assess the pharmacy business as part of integrated community health service. In conducting its activities in sales administration, purchasing administration, and administration of inventories still use manual way, it often causes delays in the process of service, inventory reports and other reports. Besides the difficulty to find medical supplies often experience an imbalance between the administrative record with the actual physical record that  because of limited manpower.  In improving the system is computerized drug inventory system, in order to produce information quickly, precisely and accurately, thus helping in the decision making process, overcoming the delayed process of achieving efficiency and effectiveness.